Epidemiology and Outcomes of Acute Respiratory Syndrome in Aged Patients with Overlap Syndrome - Celikhisar, Hakan; Ilkhan, Gulay Dasdemir (International Journal of Innovative Research in Medical Science, 2019)
Objectives: The aim of this study was to determine the complication and prognostic criteria in patients with overlap syndrome developing respiratory failure due to chronic obstructive pulmonary disease. Materials and Methods: The files of 418 patients 358 (85.6%) male and 60 (14.4%) female aged 65 years and over who were treated in İzmir Eşrefpaşa Hospital and İstanbul Okmeydanı Training Hospital intensive care units between January 2016 and January 2019 were included in the study. In this study, we retrospectively evaluated treatment modalities, complications and prognosis in aged patients with overlap syndrome. Results: It was determined that 192 (78.04 %) of the cases with complications were exitus and that 62 (36.04 %) of the 172 cases without complications were exitus. There was a statistically significant difference between the two groups with regard to mortality (p< 0.05). Conclusion: In conclusion, it was considered that the complication rate is high in aged OSAS patients with respiratory syndrome due to COPD requiring intensive care treatment and that complication development increases mortality.